2016
DOI: 10.1161/strokeaha.116.014565
|View full text |Cite
|
Sign up to set email alerts
|

Clot Burden Score on Baseline Computerized Tomographic Angiography and Intra-Arterial Treatment Effect in Acute Ischemic Stroke

Abstract: R ecanalization of the occluded vessel is the major focus of modern treatment for acute ischemic stroke. With the accumulating evidence of the additional benefit of intra-arterial treatment (IAT) in patients with anterior circulation acute ischemic stroke, a new era has started in stroke management. [1][2][3][4][5] However, even after IAT, up to 67% of patients with acute Background and Purpose-A high clot burden score (CBS) is associated with favorable outcome after intravenous treatment for acute ischemic st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(28 citation statements)
references
References 23 publications
1
25
2
Order By: Relevance
“…This study showed that the thrombus volume was significantly related to successful recanalization with an SR. Previous studies have shown inconsistent findings in terms of the association between the thrombus burden and recanalization after mechanical thrombectomy by means of an SR 6 , 9 15 . The inconsistency between the studies might be partly ascribed to differences in the method used to measure thrombus burden and the number of patients 16 .…”
Section: Discussionmentioning
confidence: 96%
“…This study showed that the thrombus volume was significantly related to successful recanalization with an SR. Previous studies have shown inconsistent findings in terms of the association between the thrombus burden and recanalization after mechanical thrombectomy by means of an SR 6 , 9 15 . The inconsistency between the studies might be partly ascribed to differences in the method used to measure thrombus burden and the number of patients 16 .…”
Section: Discussionmentioning
confidence: 96%
“…Amongst factors influencing recanalization success, clot length is an important determinant [10-12], that was scarcely assessed in the recent RCTs. Indeed, if patients were included in case of LVO on computed tomography angiography (CTA), only few studies [13,14] assessed clot length using the CTA-defined clot burden score (CTA-CBS). These analyses demonstrated a direct link between clot length, likelihood of recanalization, final infarct volumes, and 3-month neurological outcome.…”
Section: Introductionmentioning
confidence: 99%
“…It might be because of the different mechanical devices used, different methods used to determine thrombus size, and small number of cases included [ 21 , 25 - 30 ]. However, in a recent study of a relatively large number of patients who were treated with a stent retriever, higher clot burden scores were associated with increased likelihood of recanalization [ 2 ]. Smaller thrombi may be more easily retrieved with fewer attempts using a Solitaire device.…”
Section: Prediction Of Recanalization Based On Thrombus Sizementioning
confidence: 99%
“…This scoring system provides easy and rapid, yet only approximate, information on thrombus burden and can be used for the occlusion in anterior circulation only. The clot burden score is also influenced by the backflow from collateral circulation; hence, clot burden may be overestimated in cases with insufficient collaterals [ 2 ]. However, overestimated clot burden because of the lack of contrast filling due to poor collaterals may strengthen the prognostic value of this clot burden score because poor collaterals are known to be associated with poor outcomes [ 2 ].…”
Section: Practical Considerations For the Measurement Of Thrombus Sizmentioning
confidence: 99%
See 1 more Smart Citation